Uso de águas hipersalinas na produção de mudas de mangue Laguncularia racemosa (L.) Gaertn - Costa, Lucas Ramos da (2015)
Never has humanity needed much water to meet their basic needs as today, and water reuse a reality, however, still far from the ideal. Water quality is one of the factors that cause negative effect on growth and development and production of crops. In this context, the objective of this study is to enable the production of white mangrove seedlings (Laguncularia racemosa (L.) Gaertn) using hypersaline waters aiming the reforestation of degraded mangrove areas. For this, there were two experiments; the first trial was conducted between February 13 and June 3, 2014, being installed in a greenhouse located in the land sector belongs to the Federal Rural University of semiarid (UFERSA). The experimental design was a randomized block design with six treatments (S1 = 0,5; S2 = 24; S3 = 53; S4 = 77; S5 = 101e S6 = 124 dS m-1), and four replications, with 24 installments with 15 plants in each plot, a total of 360 plants. Treatments were prepared by diluting hypersaline water coming from the salt crystallisation basin with the water supply network UFERSA in order to obtain electrical conductivity of irrigation water (CEa) to their treatment. The variables were growth, fitomassas, physiological indices, Dickson quality index (DCI) and soil chemical properties. The second experiment was carried out in the field Icapuí-CE municipality, between June 30 and September 9, 2014. In general, all parameters analyzed in experiment I tended to decrease with increasing salt level in the water irrigation. The use of hypersaline water with salinity S3 = 55 dS m-1, is a viable alternative in the production of mangrove seedlings, according to the conditions of this study. The most saline treatment (S6 = 124 dS m-1), promoted the death of most of the plants in the first 100 days after treatment application. The high sodium concentrations in the substrate used not influenced the growth and development of seedlings in the greenhouse period. In the field it was found that the plants irrigated with salinities S3 = 55 dS m-1 and S4 = 77 dS m-1 showed the best grown